Higher and lower pleasures revisited: Evidence from neuroscience - Crisp, R; Kringelbach, M (Springer, 2017)
This paper discusses J.S. Mill’s distinction between higher and lower pleasures, and suggests that recent neuroscientific evidence counts against it.